The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2019)
The type specimens for names of bee taxa in the subfamilies Rophitinae, Nomiinae, and Nomioidinae of family Halictidae deposited in the Zoological Institute, Russian Academy of Sciences (St. Petersburg) are reviewed. Primary types of 63 taxa are illustrated and detailed information is provided (taxa include 20 described by F. Morawitz; 15 by Yu. Pesenko (one of them with N. Davydova and one with A. Pauly); ten by V. Popov; nine by P. Blüthgen; four by E. Eversmann; three by Yu. Astafurova; one by H. Friese, one by A. Ponomareva). A lectotype is designated for Nomia squamata Morawitz, 1894.